Factors Causing Stunting in Toddlers in The Kluwut Health Center Work Area - Ayu Khoirunnisa; Farohatus Sholichah; Mohammad Arifin (Sport and Nutrition Journal, 2025)
Stunting is one of the nutritional problems of children in Indonesia, with a high prevalence rate. Several factors cause stunting nutrition problems, including a history of low birth weight, basic immunization status, history of exclusive breastfeeding, history of complementary feeding, and the mother's employment status. The purpose of this research is to determine the relationship between the incidence of stunting and a history of low birth weight, basic immunization status, history of exclusive breastfeeding, history of giving complementary feeding, and maternal employment status. The method employed in this research is quantitative, utilizing a case-control research design. The sample in this research amounted to 98 toddlers aged 24-59 months. The instruments in this research are microtoise, questionnaire sheets, and KIA books. The statistical test used to process the data is the Chi-Square Test. The result of this research is, there is a relationship between the incidence of stunting with a history of low birth weight (p = 0.001, OR = 5.97), there is a relationship between the incidence of stunting and basic immunization status (p = 0.002, OR = 3.54), there is a relationship between the incidence of stunting and history of exclusive breastfeeding (p=0.001,  OR=10.57), there was a relationship between the incidence of stunting and the history of complementary feeding (p=0.001, OR=8.53), there was a relationship between the incidence of stunting and the mother's employment status (p =0.001, OR=9.64), so it can be concluded that there is a relationship between the incidence of stunting with a history of low birth weight, immunization status, history of exclusive breastfeeding, history of giving complementary feeding and maternal employment status.